Optical Coherence Tomography Using Polarization Information - Yamanari Masahiro (2016)
The optical coherence tomography includes a processor, wherein the processor is configured to: vectorize the Jones matrix and then convert the vectorized Jones matrix into an expanded matrix; calculate at least an eigenvalue and at least an eigenvector of the expanded matrix by performing an eigenvalue decomposition to the expanded matrix; and estimate the polarization characteristic of the subject by using at least an eigenvalue and at least an eigenvector of the Jones matrix acquired based on the at least eigenvalue and the at least eigenvector of the expanded matrix.